Reconstructing Islamic Theology through Nusantara Spirituality: a Philosophical Synthesis of Local Wisdom and Religious Tolerance - Mukari, Mukari; Rahardjo, Mudjia; Maksum, Ali; Anas, Moh. (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
This study aims to reconstruct Islamic theology through the lens of Nusantara spirituality by synthesizing local wisdom, social philosophy, and theological ethics. Using a Systematic Literature Review (SLR) approach following PRISMA 2020 guidelines, twenty-three peer-reviewed articles published between 2020 and 2025 were analyzed to identify conceptual patterns, theoretical frameworks, and methodological trends. The research focuses on three core questions: (1) how local wisdom, religious tolerance, and spirituality are conceptualized within social and theological contexts; (2) what theoretical and methodological approaches integrate Islamic theology, indigenous knowledge, and social philosophy; and (3) what gaps and directions emerge concerning spiritual–ecological ethics and dialogical spirituality.The results indicate that local wisdom functions as a moral epistemology connecting culture, faith, and social ethics. The reviewed studies demonstrate that spirituality is not confined to ritual practice but serves as a foundation for religious tolerance, ecological ethics, and community resilience. Methodologically, the combination of two-way seeing, cultural interface, and theological reflection fosters an integrative paradigm that bridges revelation (wahy) and reason (‘aql). The study introduces the concept of Filsafat Sosial Teologis Nusantara (Nusantara Theological Social Philosophy), which positions spirituality as a dialogical and ecological ethics for plural societies.In conclusion, this research contributes to the decolonization of Islamic theology by emphasizing contextual, participatory, and intercultural approaches. It provides a theoretical basis for peace education, interfaith dialogue, and sustainable social harmony rooted in the spiritual values of Nusantara.